2010
DOI: 10.1042/cs20100098
|View full text |Cite
|
Sign up to set email alerts
|

The innate immune system and diabetes mellitus: the relevance of periodontitis? A hypothesis

Abstract: About a decade ago, a hypothesis was proposed suggesting that the innate immune system, including acute-phase reactants, contribute to the development of T2DM [Type 2 DM (diabetes mellitus)] and the metabolic syndrome. In this model, it was hypothesized that the innate immune system modulates the effects of many factors, including genes, fetal programming, nutrition and aging, upon the later development of metabolic problems associated with insulin resistance. In this present article, we expand this hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…This include the gene sets caries pulp up, cell adhesion molecules, monocyte dend DN, and cytokine-cytokine receptor interaction with caries pulp up as the most significantly upregulated gene set. Interestingly, there is an increasing evidence supporting an association between periodontitis and diabetic complications [29,30] suggesting that genes related to periodontitis could play a role for the development of diabetic vasculopathy. Because the tissue in our study is without atherosclerosis and cellular infiltration, it seems that the vascular smooth muscle cells themselves may express an inflammatory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…This include the gene sets caries pulp up, cell adhesion molecules, monocyte dend DN, and cytokine-cytokine receptor interaction with caries pulp up as the most significantly upregulated gene set. Interestingly, there is an increasing evidence supporting an association between periodontitis and diabetic complications [29,30] suggesting that genes related to periodontitis could play a role for the development of diabetic vasculopathy. Because the tissue in our study is without atherosclerosis and cellular infiltration, it seems that the vascular smooth muscle cells themselves may express an inflammatory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers 14 suggested that improvement of the periodontal condition would positively affect metabolic control, while in other studies this positive effect was not evaluated. 15 Solidarity of universal pathogenetic mechanisms of inflammatory periodontal affection development, especially in patients with the metabolic syndrome, requires a complex, dynamic assessment of cytokine metabolism in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphonuclear leukocytes and alterations in the collagen metabolism could be another possible reason for higher predisposition of T2DM patients towards periodontal diseases. The formation of AGEs may influence the collagen stability and vascular integrity and could also aggregate macrophage and monocyte receptors, thereby aggravating the susceptibility to periodontitis through the stimulation of IL-1 and TNF- α [ 13 ] ( Figure 2 ). These inflammatory cytokines are known to stimulate the insulin resistance and several other chronic inflammatory complications including periodontitis [ 14 ].…”
Section: Periodontitis and Obesity/diabetes: The Two-way Complicatmentioning
confidence: 99%